Multilayered and digitally structured presentation formats of trustworthy recommendations: a combined survey and randomised trial. Issue 2 (10th February 2017) - Brandt, Linn; Vandvik, Per Olav; Alonso-Coello, Pablo; Akl, Elie A; Thornton, Judith; Rigau, David; Adams, Katie; O'Connor, Paul; Guyatt, Gordon; Kristiansen, Annette
Abstract : Objectives: To investigate practicing physicians' preferences, perceived usefulness and understanding of a new multilayered guideline presentation format—compared to a standard format—as well as conceptual understanding of trustworthy guideline concepts. Design: Participants attended a standardised lecture in which they were presented with a clinical scenario and randomised to view a guideline recommendation in a multilayered format or standard format after which they answered multiple-choice questions using clickers. Both groups were also presented and asked about guideline concepts. Setting: Mandatory educational lectures in 7 non-academic and academic hospitals, and 2 settings involving primary care in Lebanon, Norway, Spain and the UK. Participants: 181 practicing physicians in internal medicine (156) and general practice (25). Interventions: A new digitally structured, multilayered guideline presentation format and a standard narrative presentation format currently in widespread use. Primary and secondary outcome measures: Our primary outcome was preference for presentation format. Understanding, perceived usefulness and perception of absolute effects were secondary outcomes. Results: 72% (95% CI 65 to 79) of participants preferred the multilayered format and 16% (95% CI 10 to 22) preferred the standard format. A majority agreed that recommendations (multilayered 86% vs standard 91%, p value=0.31) and evidence summaries (79% vs 77%, p value=0.76) were useful in the context of the clinical scenario. 72% of participants randomised to the multilayered format vs 58% for standard formats reported correct understanding of the recommendations (p value=0.06). Most participants elected an appropriate clinical action after viewing the recommendations (98% vs 92%, p value=0.10). 82% of the participants considered absolute effect estimates in evidence summaries helpful or crucial. Conclusions: Clinicians clearly preferred a novel multilayered presentation format to the standard format. Whether the preferred format improves decision-making and has an impact on patient important outcomes merits further investigation.